A nonlinear multi-spring tire model for dynamic analysis of vehicle-bridge interaction system considering separation and road roughness - Zhang, Yao (2020)
This paper proposes a nonlinear multi-spring tire (NMST) model for dynamic analysis of vehicle-bridge interaction (VBI) system considering separation and surface roughness. First, a nonlinear single-spring tire (NSST) model is developed, which can only provide compression force rather than extension force. By introducing it into VBI system, the dynamic interaction problem considering separation and road roughness becomes a typical dynamic problem with material nonlinearity which can be easily solved by the combination of Newmark method and Newton method: the coupled governing equations never change whatever the tire separates from the bridge or not. It is more convenient because iterative process is required in conventional method to check the separation status and once separation occurs, the coupled governing equations have to change and decouple into independent equations corresponding to vehicle and bridge, respectively. It is then extended to NMST model which is more realistic because the contact surface of tire and road are of finite size instead of a point and the tire usually cannot touch the bottom of valleys in the road profile. In the numerical examples, it can be found that the dynamic responses of both bridge and vehicle obtained by NMST model are better than those obtained by NSST model because they have lower high frequency components, which is closer to the observation in the field testing. The proposed NMST model can be easily incorporated into various VBI models, which benefits for numerical study of dynamic responses of both vehicle and bridge and indirect methods to identify modal properties and local damage of bridge structures.